دور ممارسة النشاط البدني الرياضي في الرفع من أداء المصالح العملياية لدى المديرية العامة للأمن الوطني - لعروي, عابد (Institut d'Éducation Physique et Sportive - Mostaganem 2023/2024, 2024)
تهدف الدراسة إلى التعرف على دور ممارسة النشاط البدني الرياضي في الرفع من أداء المصالح العملياتية لدى المديرية العامة للأمن الوطني، ولهذا الغرض استخدمنا المنهج الوصفي على عينة متكونة من 60 رجل شرطة من المصلحة الولائية للأمن العمومي لكتيبة التدخل السريع لأمن ولاية مستغانم تم اختيارها بشكل عشوائي، لجمع البيانات استخدمنا استمارة الاستبيان، بعد جمع النتائج ومعالجتها إحصائيا تم التوصل إلى النتائج لممارسة النشاط البدني الرياضي دور في الرفع من أداء المصالح العملياتية لدى المديرية العامة للأمن العمومي من خلال تطوير اللياقة البدنية وتحسين الصحة النفسية لدى عناصرها. وعلى هذا الأساس أوصت الدراسة بضرورة إعطاء أهمية كبيرة لنشر الوعي بأهمية ممارسة الأنشطة البدنية الرياضية لدى مختلف شرائح المجتمع (الأطباء، الأساتذة، أعوان الحماية المدنية... إلخ). // // // // The Object of the study aims to identify The role of practicing physical activity in improving the performance of the operational services of the General Directorate of National Security, for this purpose, we used the method Descriptive On a sample composed of 60 policemen from the state service of public security of the Rapid Intervention Battalion for the security of the state of Mostaganem State Security Chosen as random, and for data collection, we used a tool Questionnaire After collecting the results and having treated them statistically, we conclude Practicing physical sports activity has a role in increasing the performance of the operational departments of the General Directorate of National Security by developing physical fitness and improving the mental health of its members. On this basis, the study recommended It is necessary to give great importance to spreading awareness of the importance of practicing physical sports activities among various segments of society (doctors, professors, civil protection personnel... etc.).
MES-2024-33
Keywords: النشاط البدني الرياضي - أداء المصالح العملياتية - المديرية العامة للأمن الوطني // // // physical sports activity - performance of operational services - General Directorate of National Security